2012
DOI: 10.7205/milmed-d-12-00183
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Acute Low Back Pain in Active Duty Infantry

Abstract: Although much research has been performed on occupational risk factors for low back pain, little has been published on low back pain among infantrymen. This purpose of this study is to evaluate the incidence of acute low back pain amongst active duty infantrymen as compared to a matched control population. The Defense Medical Epidemiology Database was searched and incidence rates were calculated and compared between infantry and noninfantry soldiers. Data was stratified and controlled for age, race, marital st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 35 publications
0
37
0
Order By: Relevance
“…The aim of this systematic literature review was to report LBP prevalence and incidence estimate from studies using patient electronic medical records. The included studies 2.0% M = 1.3%, F = 0.7% Spijker-Huiges et al [23] 1.0% Ernat et al [28] 3.0% Knox et al [24] 4.0% Bartholomeeusen et al [25] 5.1% (95% CI 4.9%, 5.3%), F = 5.3% (95% CI 5.1%, 5.5%), M = 4.9% (95% CI 4.7%, 5.2%) Kuijer et al [18] 5.4%; M = 5.0%, F = 4.0% Miedema et al [27] 0.024% (95% CI 0.022-0.027%), M = 0.031% (95% CI 0.028%, 0.035%), F = 0.003 (95% CI 0.002%, 0.005%) Waterman et al [29] 0.14% Moshe et al 2016 [30] 0.05% Table 4 LBP definition of the studies ICD international classification of disease, ICPC international classification of primary care…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The aim of this systematic literature review was to report LBP prevalence and incidence estimate from studies using patient electronic medical records. The included studies 2.0% M = 1.3%, F = 0.7% Spijker-Huiges et al [23] 1.0% Ernat et al [28] 3.0% Knox et al [24] 4.0% Bartholomeeusen et al [25] 5.1% (95% CI 4.9%, 5.3%), F = 5.3% (95% CI 5.1%, 5.5%), M = 4.9% (95% CI 4.7%, 5.2%) Kuijer et al [18] 5.4%; M = 5.0%, F = 4.0% Miedema et al [27] 0.024% (95% CI 0.022-0.027%), M = 0.031% (95% CI 0.028%, 0.035%), F = 0.003 (95% CI 0.002%, 0.005%) Waterman et al [29] 0.14% Moshe et al 2016 [30] 0.05% Table 4 LBP definition of the studies ICD international classification of disease, ICPC international classification of primary care…”
Section: Discussionmentioning
confidence: 99%
“…Two studies reported that the incidence of LBP in female was higher than in male [21,25]. Despite the difference in geographical locations where the studies were conducted, the incidence rates some studies have reported were approximately the same [22][23][24]28] (Table 3). 1.4% (M = 1.6%, F = 1.5%) Goetzel et al [21] 15.6% (M = 14.7%, F = 17.8%) Joud et al [20] 3.0% (M = 1.0%, F = 2.0%) Spijker-Huiges et al [23] 1.7% Edwards et al 2018 [26] 3.2%…”
Section: Incidencementioning
confidence: 99%
See 2 more Smart Citations
“…Study region: In the 31 epidemiology studies examined; 23 studies were from European countries (United States = 17, Finland = 3, Denmark = 1, Sweden = 1, and Norway = 1), two studies from Middle East countries studies (Israel = 1, Turkey = 1), and four studies from Asian countries (China = 2, Malaysia = 1, Korea = 1). Two studies did not mention the region where the studies were conducted [14,15].…”
Section: Resultsmentioning
confidence: 99%